2018
DOI: 10.1016/j.cplett.2018.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the anchorage and the catalytic properties of nanoporous TiO2 films modified with ruthenium (II) and rhenium (I) carbonyl complexes

Abstract: In this article we study the anchoring of cis-[Ru(bpyC 4 pyr)(CO) 2 (CH 3 CN) 2 ] 2+ , cis-[Ru(bpy) 2 (CO) 2 ] 2+ and cis-[Ru(bpyac)(CO) 2 Cl 2 ], onto nanoporous TiO 2 employing electropolymerization, electrostatic interaction and chemical bonding. Also, the [Re(bpyac)(CO) 3 Cl] rhenium(I) complex for chemical anchorage was analyzed. The characterization of TiO 2 /Ru(II) and TiO 2 /Re(I) nanocomposite films was performed by field emission scanning electron microscopy (FESEM), electron dispersive X-ray spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Indeed, for example, in the case of Rucarbonyl-bipyridyl complexes, the addition of an alkyl ester function on the bpy ligand has a positive influence on the catalytic activity and selectivity toward the electroreduction of CO 2 and does not prevent the formation of the active species, as we have seen above for the Re. 36,37 Note also that previous studies with rhenium triscarbonyl chloride complex with 2,2′bipyridine-4,4′-dicarboxylic acid ligand reported that this complex had no activity toward CO 2 reduction, in line with our findings. 13 Mimicking Phosphonic Anchoring Groups.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…Indeed, for example, in the case of Rucarbonyl-bipyridyl complexes, the addition of an alkyl ester function on the bpy ligand has a positive influence on the catalytic activity and selectivity toward the electroreduction of CO 2 and does not prevent the formation of the active species, as we have seen above for the Re. 36,37 Note also that previous studies with rhenium triscarbonyl chloride complex with 2,2′bipyridine-4,4′-dicarboxylic acid ligand reported that this complex had no activity toward CO 2 reduction, in line with our findings. 13 Mimicking Phosphonic Anchoring Groups.…”
Section: ■ Results and Discussionsupporting
confidence: 92%